“Death was an attempt to communicate”: Virginia Woolf's Mrs. Dalloway - Bonikowski, Wyatt (Shell Shock and the Modernist Imagination, 2013)
Septimus Warren Smith, the soldier in Virginia Woolf's Mrs. Dalloway, brings home such a revelation with him, but he is different from the other soldiers we have looked at. One of a host of characters in the complexly represented social world of London, Septimus is radically different from the others and yet part of their world. For Septimus, ‘communication’ means an ideal mode of relationship that would not have to contend with the mark of sin and crime that taints other forms of relationship. Bradshaw arrives at his diagnosis of Septimus ‘complete physical and nervous breakdown’ due to the deferred effects of shell shock by way of the principles of Proportion and Conversion, which guide legal and medical discourse as well as the movement of civilization. Septimus, in Bradshaw's hands, becomes a mere ‘case’, and the term ‘shell shock’ is marked as an inadequate label that confines Septimus in an explanatory framework dictated by reason and its dominating darker side. Septimus Warren Smith, the soldier in Virginia Woolf's Mrs. Dalloway, brings home such a revelation with him, but he is different from the other soldiers we have looked at. One of a host of characters in the complexly represented social world of London, Septimus is radically different from the others and yet part of their world. For Septimus, 'communication' means an ideal mode of relationship that would not have to contend with the mark of sin and crime that taints other forms of relationship. Bradshaw arrives at his diagnosis of Septimus 'complete physical and nervous breakdown' due to the deferred effects of shell shock by way of the principles of Proportion and Conversion, which guide legal and medical discourse as well as the movement of civilization. Septimus, in Bradshaw's hands, becomes a mere 'case', and the term 'shell shock' is marked as an inadequate label that confines Septimus in an explanatory framework dictated by reason and its dominating darker side.